2017
DOI: 10.1002/ece3.2890
|View full text |Cite
|
Sign up to set email alerts
|

Increasing copper alters cellular elemental composition (Mo and P) of marine diatom

Abstract: The elemental composition (surface adsorbed and internalized fraction of Cu, Mo and P) in marine phytoplankton was first examined in cultures of the diatom Phaeodactylum tricornutum which were exposed to various levels of Cu concentrations ranging from 0.25 to 16 μmol/L with equivalent free [Cu2+] concentrations of 0.4–26 nmol/L. We observed an acceleration of algal growth rates (20–40%) with increasing ambient Cu levels, as well as slightly increased levels of internalized Cu in cells (2–13 × 10−18 mol/cell) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 82 publications
(135 reference statements)
0
2
0
1
Order By: Relevance
“…Cu holds an important role in the photosynthetic and respiratory electron transport in phytoplankton 48 . Extended Redfield ratios of marine and freshwater phytoplankton centre around a total Cu content of 10 −16 –10 −18 mol cell −1 and a Cu:C ratio of ~10 −6 49 51 . This Cu:C ratio is similar to the theoretical stoichiometric ratio of a MOB cell, but phytoplankton, being significantly larger than MOB, contains much more Cu per cell (factor 10 2 –10 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cu holds an important role in the photosynthetic and respiratory electron transport in phytoplankton 48 . Extended Redfield ratios of marine and freshwater phytoplankton centre around a total Cu content of 10 −16 –10 −18 mol cell −1 and a Cu:C ratio of ~10 −6 49 51 . This Cu:C ratio is similar to the theoretical stoichiometric ratio of a MOB cell, but phytoplankton, being significantly larger than MOB, contains much more Cu per cell (factor 10 2 –10 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen and phosphorus availability altered Cu sensitivity in Ditylum brightwellii, Thalassiosira pseudonana, and Phaeodactylum tricornutum (Rijstenbil and Wijnholds, 1991;Rijstenbil et al, 1998;Wang D. et al, 2017), and mediation of Cu toxicity by high silicic acid concentrations was observed in T. pseudonana and Skeletonema costatum (Morel et al, 1978;Rueter et al, 1981). Likewise, the availability of other trace metals can ameliorate Cu toxicity.…”
Section: Macronutrient and Micronutrient Availability Should Be Consimentioning
confidence: 95%
“…Cu is essential for many physiological processes in phytoplankton, including electron-transfer reactions and high-affinity Fe transport systems, therefore low-Cu concentrations can also limit phytoplankton growth, as observed in the coccolithophore and T. oceanic [7]. Therefore, slight increases in ambient Cu concentrations have been shown to trigger the growth of P. tricornutum [25]. We found that increased Cu concentrations appeared to stimulate the growth of T. pseudonana at lower concentrations, which is consistent with previous studies [43,44].…”
Section: Growth Ratesmentioning
confidence: 99%
“…Consequently, diatoms were used as optimal-biological models to investigate ecotoxicological and environmental effects arising from stressors on marine ecosystems [21][22][23]. Cu influences phytoplankton growth [24,25] and cellular-elemental stoichiometry, as well as a range of biochemical process such as pigmentation, photosynthesis and biochemical composition [26]. Furthermore, variation in physicochemical factors including temperature, salinity and pH, can impose additional stress on marine organisms, while also influencing metal contaminants, thereby affecting their availability and toxicity to organisms.…”
Section: Introductionmentioning
confidence: 99%